Kebijakan Hukum Pidana Terhadap Driver Transportasi Online Yang Melakukan Kecurangan Menurut Undang-Undang Informasi Dan Transaksi Elektronik (Studi Putusan Pengadilan Negeri Pemalang Nomor 82/Pid.Sus/2018/Pn Pml Dan Putusan Pengadilan Negeri Denpasar Nomor 226/Pid.Sus/2020/Pn Dps) - Indah Widyarantika Zebua (Iuris Studia: Jurnal Kajian Hukum, 2021)
Online transportation is now growing rapidly. The more people who want to become partners, the more competition for online transportation itself will be. So that it causes many partners to commit fraud or cheating. Various modes of cheating are committed by several drivers, including: Fake GPS, Incentives, Fake apps. Based on the above problems, the problems of this thesis are as follows: Is fraud committed by online transportation drivers a criminal act? What is the criminal law policy against online transportation drivers who commit fraud according to the Electronic Information and Transaction Law? What is the judge's consideration of online transportation drivers who commit fraud according to the Electronic Information and Transaction law (Study of Pemalang District Court Decision Number 82 / Pid.Sus / 2018 / PN PML and Denpasar District Court Decision Number 226 / Pid.Sus / 2020 / PN Dps)? The research method used is normative legal research. The nature of research It is descriptive analytical with a Legislative Approach (sculpture approach). In normative legal research, the data used are secondary data. Secondary data obtained by conducting research on primary legal materials, secondary legal materials and tertiary legal materials. The criminal act of online transportation fraud is regulated in Article 51 paragraph (1) in conjunction with Article 35 of Law Number 11 of 2008 concerning Electronic Information and Transactions has been amended by Law Number 19 of 2016 in conjunction with Article 55 paragraph (1) 1st of the Criminal Code jo Article 64 paragraph (1) of the Criminal Code